Dari Hamba Musa Menjadi Hamba Tuhan: Kajian Teologis Naratif Transformasi Identitas Yosua - Tawera, Kezia Thesalonika Meilani; Diobhema Mongkar, Sindhunata (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2025)
This study examines the shift in Joshua’s designation from mesharet Mosheh (servant of Moses) in Joshua 1:1 to ebed YHWH (servant of the LORD) in Joshua 24:29 as a significant theological marker. This change is not merely a linguistic variation but part of the construction of leadership identity that highlights a transition of authority—from human recognition to divine acknowledgment. The primary aim of this research is to uncover the theological meaning embedded in these titles. The study employs a qualitative approach through library research, applying a narrative-theological exegetical method. The research process involves collecting biblical texts and academic literature, reducing the data to focus on key terms, conducting exegetical analysis that includes historical, morphological, semantic, and narrative aspects, and drawing theological conclusions. The findings reveal that the title mesharet Mosheh reflects Joshua’s formative stage as Moses’ assistant, whereas the title ebed YHWH affirms his authority as Israel’s leader recognized by God. This study emphasizes the function of these titles as narrative-theological instruments rather than mere historical records.